Pengembangan Proses Pembelajaran Produktif Melalui Diskusi dan Presentasi Kelompok untuk Kompetensi Keahlian Teknik Kendaraan Ringan SMK N 1 Kaligondang Purbalingga - Suwardi, Suwardi; Sahria, Yoga; Santosa, Budi (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to determine the improvement of learning quality through discussion methods and group presentations in productive subjects of Light Vehicle Engineering at SMKN1 Kaligondang. The approach used is Classroom Action Research (PTK) with a focus on developing productive learning materials through group discussions and presentations held in class XI TKR 3 semester 4 of the 2024/2025 school year. The method used is classroom action research with two cycles. The first cycle involves group discussion activities and presentations, while the second cycle adds the treatment of Achievement Motivation Training. The results of the study showed an increase in students' understanding and skills after group discussions and presentations. In addition, with the addition of Treatment Achievement Motivation Training, students become more motivated and active in the learning process. Data collection was carried out by observation sheets, student activity questionnaires and documentation checklists. The data obtained in this study was analyzed using a descriptive analysis technique with percentages, besides that it was also based on the reflection of each cycle of action. This study involved several variables, namely: 1) the quality of learning materials, 2) students' involvement in group discussions, 3) students' presentation skills, and 4) improvement of light vehicle engineering competence. The results of the study showed a significant improvement in the quality of learning and student competence after the intervention.